2018
DOI: 10.3390/su10030809
|View full text |Cite
|
Sign up to set email alerts
|

The Post-Intervention Persistence of Energy Conservation Behaviors: An Evaluation of the ‘Start Green’ Program

Abstract: For more than four decades, behavioral intervention programs informed by psychology have been employed to increase pro-environmental behaviors. However, there has been little evidence for the post-intervention durability of target behaviors. The few studies that have conducted such evaluations have found that improvements often return to baseline levels post-intervention. This study evaluated the durability of home energy conservation behaviors before, during, and after a community based multi-technique interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…This study differs from the existing research in two fundamental aspects, both of which concern the assessment of pro-environmental behaviour. Most empirical studies have so far taken into account individual types of behaviour, such as separate waste collection [19], energy conservation [20], or the generally understood pro-environmental behaviour [21]. In this study, pro-environmental behaviour includes several aspects, including the use of renewable energy, waste separation, and the use of public transport.…”
Section: Introductionmentioning
confidence: 99%
“…This study differs from the existing research in two fundamental aspects, both of which concern the assessment of pro-environmental behaviour. Most empirical studies have so far taken into account individual types of behaviour, such as separate waste collection [19], energy conservation [20], or the generally understood pro-environmental behaviour [21]. In this study, pro-environmental behaviour includes several aspects, including the use of renewable energy, waste separation, and the use of public transport.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Han et al (2020) explored the influence of normative, affective, and habitual factors on guests' water conservation and towel reuse intentions, and another study revealed the impact of environmental awareness on young vacationers' recycling and conservation intentions [19]. These studies have significant contributions to both promoting sustainable behaviour (e.g., [20]) and building and urban energy performance modelling (e.g., [21,22]). However, the psychological mechanisms behind hotel guests' energy conservation behaviour remain underexplored.…”
Section: Introductionmentioning
confidence: 99%
“…If we had the quantity of information for more fine‐grained analysis, our results would have been more robust. Finally, the extent to which behavior change persists after the intervention has ceased needs investigation (Burns & Savan, 2018 ; Byerly et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%